2020
DOI: 10.1177/1074248420941675
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Mellitus and Noncardiac Atherosclerotic Vascular Disease—Pathogenesis and Pharmacological Treatment Options

Abstract: Diabetes mellitus (DM) is also a cause of cardiovascular (CV) disease (CVD). Addressing the atherosclerotic CVD (ASCVD) burden in DM should reduce premature death and improve quality of life. Diabetes mellitus–associated ASCVD can lead to complications in all vascular beds (carotids as well as coronary, lower extremity, and renal arteries). This narrative review considers the diagnosis and pharmacological treatment of noncardiac atherosclerotic vascular disease (mainly in patients with DM). Based on current kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 146 publications
(255 reference statements)
0
9
0
Order By: Relevance
“…Duration of DM also increases the risk of CHD death independently of coexisting risk factors (RFs) [3] and ASCVD affects approximately 32.2% of all T2DM patients [4]. Addressing the ASCVD burden in DM should improve quality of life and reduce premature death [5].…”
Section: Letter To the Editormentioning
confidence: 99%
“…Duration of DM also increases the risk of CHD death independently of coexisting risk factors (RFs) [3] and ASCVD affects approximately 32.2% of all T2DM patients [4]. Addressing the ASCVD burden in DM should improve quality of life and reduce premature death [5].…”
Section: Letter To the Editormentioning
confidence: 99%
“…When it comes to atherosclerotic CV disease, we should pay more attention to diabetic mellitus (DM), since DM is an important risk factor of atherosclerotic CV diseases, including CAD and other non-cardiac atherosclerotic diseases. Pharmacological treatment for this group of patients is of great interest, and tailored therapies are needed [ 24 ]. A recent review demonstrated that cilostazol might help to reduce diabetes-associated microvascular complications [ 25 ], but studies using cilostazol in patients with DM for macrovascular events were lacking.…”
Section: Introductionmentioning
confidence: 99%
“… 10 Vascular endothelial dysfunction also occurs in type 2 diabetes mellitus (T2DM) at early stage and triggers consecutive systemic inflammation. 11 These subtle pathological changes gradually contribute to vascular complications such as IMT, atherosclerosis and increase the risk of poor prognosis in stroke. 12 , 13 …”
Section: Introductionmentioning
confidence: 99%